WO3/CoWO4 nanocomposite synthesis using a facile co-precipitation method for enhanced photocatalytic applications. (July 2021) - Thilagavathi, T.; Venugopal, D.; Marnadu, R.; Chandrasekaran, J.; Thangaraju, D.; Palanivel, Baskaran; Hamdy, Mohamed S.; Shkir, M.; Ali, H. Elhosiny
Abstract: In this work, pure tungsten oxide (WO3 ) nanoparticles (NPs) and WO3 /CoWO4 nanocomposites (NCs) with various cobalt concentrations from 5 to 20 wt% were prepared via a co-precipitation process and subsequent annealing at 600 °C. All the synthesized samples were characterized by different techniques to study their structural, morphological, elemental, and optical properties and also to verify the conversion of WO3 NPs to WO3 /CoWO4 NCs. X-ray diffraction results confirmed the existence of a stable monoclinic phase for pure WO3 NPs and that no phase change occurs even after the formation of CoWO4 . The average crystallite sizes calculated for pure WO3 NPs and 20 wt% WO3 /CoWO4 NCs were approximately 34 and 17 nm, respectively. Field-emission scanning electron microscopy revealed that pure WO3 consists of nanoparticles as well as some nanoplates of size in the 30 nm diameter range. On Co doping of WO3, the size seems decrease and reveals very small NPs of size below 20 nm. Energy-dispersive X-ray spectroscopy spectra showed the persistence of chemical elements and their amount before and after the inclusion of cobalt. The chemical composition and the oxidation state of the elements on the surface of the synthesized NPs and NCs were investigated by X-ray photoelectron spectroscopy. The type of functional groups and their corresponding vibrational modes were identified by Fourier transform infrared spectroscopy. UV–visible studies were used to calculate the bandgap ( E g ) of pure WO3 NPs and WO3 /CoWO4 NCs by means of Kubelka-Munk function plots. There was a reduction in E g from 2.61 eV for pure WO3 NPs to 2.51 eV for 20 wt% Co NCs. In photoluminescence studies, the intensity of the emission peaks of WO3 /CoWO4 NCs showed a decreasing trend in comparison with pure WO3 NPs. The formation of WO3 /CoWO4 NCs effectively controls the charge carrier (electron-hole) recombination. Hence, an appreciable enhancement in the photocatalytic degradation of the toxic dye methylene blue (C16 H18 N3 SCl) of up to 86.5% was accomplished with WO3 /CoWO4 NCs (20 wt% Co sample) under irradiation with a UV-A light source. Graphical abstract: Toxic dye degradation profile of the prepared nanocomposites and proposed mechanism of dye degradation. Image 1 Highlights: A facile and low-cost co-precipitation method was used to prepare WO3 nanoparticles and WO3 /CoWO4 nanocomposites. Structural and compositional analyses proved the synthesis of WO3 and WO3 /CoWO4 nanocomposites. Small nanoparticles was proved via high-resolution transmission electron microscopy, and selected-area electron diffraction analysis. A reduction in the band gap from 2.61 to 2.51 eV was found on Co doping of WO3 . Higher photocatalytic activity for degradation of harmful methylene blue was found for WO3 /CoWO4 .